PENGARUH TERPAAN GREEN PROMOTION DAN PERSEPSI MANFAAT TERHADAP CAMPAIGN WASTE DOWN BEAUTY UP SOCIOLLA - Ardelia Fitriani, Neysa; Pradekso, Tandiyo; Naryoso, Agus (Interaksi Online, 2024)
Sociolla, one of the most famous cosmetic stores in Indonesia, has launched an environmentally friendly campaign called Waste Down Beauty Up. In 2022, there will be 6.8 million tons of cosmetic waste, 70% of which is not processed properly. This motivated Sociolla to launch an environmentally friendly campaign by offering various benefits so as to motivate people to participate in the campaign. This research aims to find out whether the influence of green promotion exposure and perceived benefits on participation intention campaign Waste Down Beauty Up. This research is a type of explanatory research using non-probability sampling techniques. The number of respondents was 103 people with the characteristics of women, at least 17 years old, Sociolla consumers, had never participated in the Waste Down Beauty Up campaign, and had ever seen the Waste Down Beauty Up campaign promotion. The theories used are Cognitive Response Theory, Participatory Culture Theory, and Concept 3A (Awareness, Attitude, Action). The research results show that green promotion exposure can influence participation intention the Waste Down Beauty Up campaign and perceived benefits can participation the Waste Down Beauty Up campaign. The researcher's recommendation for Sociolla is to increase the frequency of promotions on social media, such as Instagram and TikTok. Not only that, Sociolla also needs to emphasize environmental problems caused by the accumulation of cosmetic packaging container waste through promotional activities on Sociolla's social media.